Singapore: The little giant of Southeast Asia (2013)
This article aims to show an overview of Singapore, a country that today is recognized worldwide as a financial and business center for the stability of its government and the strength of its economy. In addition, it seeks to expose some of the achievements made by this economy and the type of policies implemented to achieve the status it enjoys today. Subsequently, the advances in bilateral relations between Colombia and Singapore are presented, to finally conclude with an opinion on what Colombia should learn from Singapore to achieve economic development that allows to raise the standard of living of its inhabitants, being key to this process the education of its population and the benefit that Foreign Direct Investment (FDI) brings to countries that know how to take advantage of it, from the point of view of knowledge absorption.